(untitled) (Ibrahim Cardiac Medical Journal, 2015)
Background and Objectives: The cervical screening algorithm for benign cellular changes on the Pap smear recommends treatment of infection if indicated and a repeat Pap smear should be done in 4-6 months time. If repeat smear suggests continuation of inflammatory changes, the patient is subjected to colposcopic evaluation. During this lag time, a good number of patients in their premalignant stage may be missed or undergo malignant transformation. Recent studies advocate a repeat Pap smear if treatment of infection for 2-4 weeks does not respond and if repeat Pap smear suggests persistence of inflammatory changes, the patient should be evaluated colposcopically to determine the rate of undetected cervical intraepithelial neoplasia/dysplasia in patients with persistent inflammatory Pap smear. The present study was undertaken to that end. Patients & Methods: This cross-sectional study was carried out in the Department of Obstetrics and Gynaecology, Institute of Child & Mother Health (ICMH), Dhaka, over a period of 12 months from July 2013 to June 2014. Patients with two consecutive reports of inflammatory cellular changes without atypia on Pap smears despite anti-inflammatory therapy were the study population. A total of 1456 women underwent Paps test at the above mentioned place during the study period for gynaecological problems. Of them 312(21.4%) were reported as ‘inflammatory cellular changes’. After giving anti-inflammatory treatment most of them were cured leaving 128(8.8%) cases with repeat report of inflammatory cellular changes on Pap smear and hence were included in the study. Results: The mean age of the enrolled women was 32.6 ± 7.2 years. Mean age of the patients at marriage and mean age at first child birth were 14.9 years (range: 12-23 years) and 16.5 years (range: 13-26 years) respectively. Majority (94.5%) of the patients were multipara. Of the 128 women, 66(51.6%) were colposcopically positive for CIN. Of them over two-thirds (68.2%) were graded as CIN-1, 25.8% as CIN-2, and 6% as CIN-3. Histological evaluation of biopsy material taken from these 66 cases revealed 25(37.9%) with abnormal cytology (3-CIN-1, 18-CIN-2 and 4 with invasive carcinoma) which accounts for 19.5% of the persistent Paps smear cases. Comparing age at marriage, age at first childbirth and parity between patients with CIN (including invasive disease) and without CIN revealed that the former group married and experienced child birth relatively earlier than the latter group (p = 0.001 and p < 0.001 respectively). The average parity was also significantly higher in the CIN group. Conclusions: A high proportion of patients with persistent inflammatory Pap smear can harbour CIN and sometimes even early stage of invasive carcinoma. So patients with persistent inflammatory cellular changes on Pap smear if does not respond to treatment, they should be subjected to a repeat smear within 2-4 weeks and if inflammatory changes continue, they should be immediately evaluated by colposcopy. Ibrahim Cardiac Med J 2014; 4(1): 9-15